Caracterização e análise das propriedades da fibra de Macambira (Bromelia Laciniosa) - Pimentel, Juliana Rangel de Morais (2012)
Concern for the environment and the exploitation of natural resources has motivated the development of research in lignocellulosic materials, mainly from plant fibers. The major attraction of these materials include the fact that the fibers are biodegradable, they are a renewable natural resource, low cost and they usually produce less wear on equipment manufacturing when compared with synthetic fibers. Its applications are focused on the areas of technology, including automotive, aerospace, marine, civil, among others, due to the advantageous use in economic and ecological terms. Therefore, this study aims to characterize and analyze the properties of plant fiber macambira (bromelia laciniosa), which were obtained in the municipality of Ielmo Marino, in the state of Rio Grande do Norte, located in the region of the Wasteland Potiguar. The characterization of the fiber is given by SEM analysis, tensile test, TG, FTIR, chemical analysis, in addition to obtaining his title and density. The results showed that the extraction of the fibers, only 0.5% of the material is converted into fibers. The results for title and density were satisfactory when compared with other fibers of the same nature. Its structure is composed of microfibrils and its surface is roughened. The cross section has a non-uniform geometry, therefore, it is understood that its diameter is variable along the entire fiber. Values for tensile strength were lower than those of sisal fibers and curauá. The degradation temperature remained equivalent to the degradation temperatures of other vegetable fibers. In FTIR analysis showed that the heat treatment may be an alternative to making the fiber hydrophobic, since, at high temperature can remove the hemicellulose layer, responsible for moisture absorption. Its chemical constitution is endowed with elements of polar nature, so their moisture is around 8.5% which is equivalent to the percentage of moisture content of hydrophilic fibers. It can be concluded that the fiber macambira stands as an alternative materials from renewable sources and depending on the actual application and purpose, it may achieve satisfactory results